2020
DOI: 10.1167/iovs.61.11.14
|View full text |Cite|
|
Sign up to set email alerts
|

Pressure-Induced Changes in Astrocyte GFAP, Actin, and Nuclear Morphology in Mouse Optic Nerve

Abstract: Purpose To conduct quantitative analysis of astrocytic glial fibrillary acidic protein (GFAP), actin and nuclei distribution in mouse optic nerve (ON) and investigate changes in the measured features after 3 days of ocular hypertension (OHT). Method Serial cross-sections of 3-day microbead-induced OHT and control ONs were fluorescently labelled and imaged using confocal microscope. Eighteen structural features were measured from the acquired images, including GFAP cover… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
34
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(35 citation statements)
references
References 64 publications
1
34
0
Order By: Relevance
“…By analogy, it suggests that the astrocyte process area of a zone without AQP4 channels would have lower astrocyte area. Indeed, in quantitative analysis of astrocyte area as a proportion of ON tissue in fixed, cryosectioned mouse tissue, we found that the astrocyte area in the UON, which is devoid of AQP4, is less than half that of the MON [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…By analogy, it suggests that the astrocyte process area of a zone without AQP4 channels would have lower astrocyte area. Indeed, in quantitative analysis of astrocyte area as a proportion of ON tissue in fixed, cryosectioned mouse tissue, we found that the astrocyte area in the UON, which is devoid of AQP4, is less than half that of the MON [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…Alterations in the ECM arrangement of the lamina cribrosa and the peripapillary sclera cause changes in the mechanical support of this region and thereby affect the mechanosensation mechanisms of astrocytes by their junctional complexes upon IOP elevation [ 55 ]. In DCN-deficient mice we reported previously that the increase in IOP and the loss of ON axons is accompanied by an enhanced expression and synthesis of GFAP by astrocytes [ 32 ], which, from a biomechanical perspective, would cause together with ECM changes an increase in tissue stiffness [ 62 , 63 ]. Up to now, there has been no data on the amounts of DCN in the ONH of glaucoma patients, which would be of great interest since increased amounts of TGF-β are known to be present in the ONH [ 26 , 28 , 47 ]…”
Section: Discussionmentioning
confidence: 99%
“…The assumption of a stiffer PPS than the AL is supported by strain measurements herein and by the tissues' load-bearing components, predominantly collagen fibres in the PPS and astrocytic processes in the AL [44,45]. The astrocytic processes align predominantly in-plane across the AL and can span the entirety of the AL [46–49]. The AL periphery has denser astrocytic processes, thicker filamentous cytoarchitecture and transcellular contacts through their basement membranes with the PPS [49,50].…”
Section: Discussionmentioning
confidence: 82%
“…The astrocytic processes align predominantly in-plane across the AL and can span the entirety of the AL [46–49]. The AL periphery has denser astrocytic processes, thicker filamentous cytoarchitecture and transcellular contacts through their basement membranes with the PPS [49,50]. This morphology could make the AL stiffer peripherally, resulting in locally smaller tensile strain.…”
Section: Discussionmentioning
confidence: 99%